Fish oil and probiotic food supplements: Consumptions and attitudes of pregnant women in four European countries - Jaakkola, Kristiina (My University, 2024)
Fish oil and probiotic supplements may be of benefit during pregnancy, but no information on their use across geographically and socioeconomically diverse countries exists. The aim was to investigate 1) usage of fish oil and probiotic food supplements by pregnant women, 2) awareness amongst pregnant women of the prevailing recommendations and 3) the characteristics of the users and their beliefs regarding potential health effects of food supplement use, and to compare these variables between women from four European countries. Poland have included in their dietary recommendations for pregnant women to consume fish oil during pregnancy, whilst others, including Finland, Italy and the United Kingdom (UK), consider that the scientific evidence is insufficient to set a recommendation for this specific group of individuals. Due to insufficient scientific evidence a general recommendation on the use of probiotics during pregnancy is not included in the guidance from many countries including those studied in this research. The survey was carried out by online questionnaires aimed at Finland, Italy, Poland, and the UK, further product information of the supplements (i.e. product name, producer, trademark, nutritional content, and the dose taken) used was collected from participants. Half of the pregnant women used fish oil supplements, while probiotic use was less frequent, further differences between countries were observed. Not all pregnant women were familiar with the prevailing recommendations or potential health effects of these food supplements, which should be considered in the diet counselling provided during future health care visits to optimise maternal and neonatal health.
Keywords: fish oil, probiotics, pregnancy, recommendations